USING COST ACCOUNTING AS THE BASIS FOR SELLING PRICE DETERMINATION: THE CASE FOR KANSA BAKERY - Hizkia Anugerah Pramandiri; Agung Praptapa; Eliada Herwiyanti (Universitas Katolik Indonesia Atma Jaya, 2017)
The development of Micro, Small, and Medium Enterprises (MSMEs) in various countries including Indonesia is rising rapidly. The tightness of competition in the business world requires companies to improve efficiency in calculating production costs because it is the base for determining sales price.This case study employs qualitative method. CV Kansa Bakery, producer of steamed sponge cake was studied. Miles and Huberman's technique was utilized for data analysis, the three stages were data reduction, data display, and conclusion. The research was conducted by comparing full-costing and cost-plus pricing methods.Calculation shows that full-costing method gives different results compared to the when compared to the existing method used by Kansa Bakery. This resulted from the fact that Kansa did not apply proper accounting method in classifying and charging factory overhead to their product. This affects selling price determination and profit generation.